Clockwise Torque of Sliding Hip Screws: Is There a Right Side?. (November 2020) - Würdemann, Franka S.; Poolman, Rudolf W.; Krijnen, Pieta; Bzovsky, Sofia; Sprague, Sheila; Kaptein, Bart L.; Hegeman, Johannes H.; Schemitsch, Emil H.; Bhandari, Mohit; Swiontkowski, Marc; Schipper, Inger B.
Abstract : Objectives: This study evaluated whether patients with a left-sided femoral neck fracture (FNF) treated with a sliding hip screw (SHS) had a higher implant failure rate than patients treated for a right-sided FNF. This was performed to determine the clinical relevance of the clockwise rotational torque of the femoral neck lag screw in a SHS, in relation to the rotational stability of left and right-sided FNFs after fixation. Methods: Data were derived from the FAITH trial and Dutch Hip Fracture Audit (DHFA). Patients with a FNF, aged ≥50, treated with a SHS, with at least 3-month follow-up data available, were included. Implant failure was analyzed in a multivariable logistic regression model adjusted for age, sex, fracture displacement, prefracture living setting and functional mobility, and American Society for Anesthesiologists Class. Results: One thousand seven hundred fifty patients were included, of which 944 (53.9%) had a left-sided and 806 (46.1%) a right-sided FNF. Implant failure occurred in 60 cases (3.4%), of which 31 were left-sided and 29 right-sided. No association between fracture side and implant failure was found [odds ratio (OR) for left vs. right 0.89, 95% confidence interval (CI) 0.52–1.52]. Female sex (OR 3.02, CI: 1.62–6.10), using a mobility aid (OR 2.02, CI 1.01–3.96) and a displaced fracture (OR 2.51, CI: 1.44–4.42), were associated with implant failure. Conclusions: This study could not substantiate the hypothesis that the biomechanics of the clockwise screw rotation of the SHS contributes to an increased risk of implant failure in left-sided FNFs compared with right-sided fractures. Level of evidence: Therapeutic Level II.See Instructions for Authors for a complete description of levels of evidence.